Comunicación asertiva y relaciones interpersonales de los usuarios registrados en la Oficina Regional de Atención a Personas con Discapacidad, Trujillo, 2022 - Solano Herrera, Yussith Jamilei (2023)
This thesis entitled Assertive communication and interpersonal relationships of registered users in the Regional Office of Attention to People with Disabilities, Trujillo, 2022, aims to analyze the influence of assertive communication in the interpersonal relationships of users with disabilities of this Office. For this reason, a sample of 70 registered users was taken, due to which most of them are female, between the ages of 20 and 39 years old. The methods used in this research were analytical-synthetic, inductive-deductive and statistical, likewise, the techniques used were the interview and the survey, since they allowed collecting quantitative and qualitative information in order to develop the thesis with a correct analysis. In addition, the r instruments used are the interview guide and record and the survey questionnaire, reaching the data on the indicators and variables identified to measure the present research. Thus, the results obtained show that assertive communication has a positive influence on the interpersonal relationships of the users registered in the Regional Office of Attention to Persons with Disabilities, due to the fact that 37.14% of the users practice constant dialogue in order to improve active listening and establish assertive communication, as well as taking into account that 38.57% of the users feel part of the group, which is necessary to continue strengthening their interpersonal relationships. The role of the Social Worker is essential to continue promoting assertive communication in users with disabilities and thus form their interpersonal relationships to improve the welfare of each of them.